Penile Urethral Hypospadias with Two Fistulae and Diverticulum in a Saanen Kid - Areeg Mohamed Almubarak; Rihab Mohamed Abdelghafar; Ahmed Abdelrahim Gameel; Nuha Muatasim Osman (Case Reports in Veterinary Medicine)
Hypospadias is a rare congenital defect reported in most animal species and humans. This case study reports a hypospadiac case in a goat kid with urethral diverticulum diagnosed in Sudan for the first time. A 45-day-old male kid was presented to the Veterinary Teaching Hospital, College of Veterinary Medicine, Sudan University of Science and Technology (SUST), with a history of an increasing prescrotal swelling. At presentation in the clinic the kid was bright and alert and the vital parameters were within the normal physiological range. Ultrasonography was performed to assess the integrity of the urinary system using (3.5–5) MHz curvilinear probe and it revealed normal kidneys and a distended urinary bladder. The kid was referred to surgery and two hypospadiac urinary fistulae were found. One fistula was sutured and the other was not corrected due to catheterization failure.